Childhood Candida Infections: Single Center Experience - (:unkn) unknown (CUKUROVA UNIV, FAC MEDICINE, 2015)
Purpose: Candida is third place in the list of factors in healthcare-related bloodstream infections in the United States of America and Europe. Invasive fungal infections increase the hospital stay, costs and morbidity of critical and immunosuppressed patients. The aim of this study is to investigate the types, risk factors and clinical progress of Candida infections and to contribute to the insufficient literature on this topic. Material and Methods: The files of 29 pediatric patients with invasive Candida infection between January 2011 and January 2013 at Marmara University Faculty of Medicine were retrospectively investigated. Results: Twenty-nine patients were diagnosed with Candida infection. Of these patients 17 were male (59%) and 12 were female (41%). Eleven patients were less than a year old (38%), 9 were between 1-5 years (31%) and 9 were above the age of five (31%). The most important underlying disease malignancies were congenital heart disease and neurological diseases. Candida growth was determined in the blood cultures of 17 patients, the urine cultures of 10 patients and in the cerebrospinal fluid of one patient. While the most commonly used anti-fungal agent was fluconazole (51.7%), others used were caspofungin (41.3%) and amfoterisin B (13.7%). No isolated Candida strain showed resistance to anti-fungal agents. Treatment was clinically and microbiologically 96.5% successful. Conclusions: Fluconazole still appears to be an effective treatment choice we believe there is a necessity to review the Minimal Inhibitory Concentration (MIC) values for anti-fungal agents.
Keywords: Fluconazole; Antifungal; Candida; Child; BLOOD-STREAM INFECTIONS; RISK-FACTORS; PEDIATRIC-PATIENTS; HOSPITALIZED ADULT; EPIDEMIOLOGY; MULTICENTER; THERAPY